EPIDEMIOLOGICAL ANALYSIS OF CARIES IN CHILDREN DURING OUT-PATIENT TREATMENT IN DONETSK REGION - A. V. Makhniova (Ukrainian Medical Stomatological Academy, 2015)
Relevance. Frequency of tooth decay in children doesn't have a tendency to decline. Frequency of turning to the therapeutic stomatological clinic concerning caries is 40-50 % of the general amount of patients. Frequency of the complicated temporary teeth caries in children under 7 was 37.3 %. Growth of prevalence of the complicated temporary teeth caries in children seeking stomatological treatment increased from 9.1 % to 69.1 %. The purpose of this work is an epidemiological analysis of caries in children during out-patient treatment at the dentist`s in Donetsk region. Material and methods. The data of 33 697 children of three age groups were analyzed. There were such parameters: age; general amount of children, living in the district of dental service; amount of children seeking stomatological treatment; frequency of turning to the therapeutic stomatological clinic; amount of sick children; morbidity; amount of children with a diagnosis of dental caries. Morbidity of caries, prevalence of caries, intensity of caries, coefficient of intensity of caries were calculated. Results. Decreased amount of children with age (48 554; 59 402 и 28 549 children according to age groups, totally 136 505 children) has been found out. Reliable distinctions of frequency of turning to the therapeutic stomatological clinic (appealing children amount - the general amount of this age group children relation) in three age groups, exposing was not succeeded (24.6 %; 24.6 % and 25 % according to age, the general appealability was 24.7 %; p = 0.609). While analyzing morbidity (sick children amount - the general amount of this age group children relation) reliable distinctions of three age groups are exposed (21.9 %; 23.6 % and 22.5 %; general morbidity was 22.8 %; p < 0.001). In the second group intensity of caries was less than in the first group by 29.3 % (р < 0.001), and in the third group - by 0.66 % (р < 0.001), than in the second one and by 29.9 % (р < 0.001), than in the first one.The coefficients of intensity according to groups are equal: 1.88; 1.59 and 1.58; general coefficient is 1.69 (p < 0.001). Conclusion. The children of all groups don't have full and timely oral cavity sanitation. This is the result of abolition of the prophylactic stomatological help providing system for children. An increase of general morbidity with age shows that not enough prophylactic and dental sanitation are presented, which can result into the premature extraction of temporary teeth and affect the process of development and eruption of the permanent teeth. Also, a substantial decline of intensity of caries (by three times) with age shows the efficiency of dental caries treatment conducted by the dentists of child's policlinic.